2022
DOI: 10.7759/cureus.30993
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Induced Thrombocytopenia: A Brief Literature Review and Case Report

Abstract: With sporadic surges of COVID-19, medical professionals are continuously expanding their knowledge and contributing to medical literature through experiences and research. We present a rare case of a 65-year-old Hispanic male diagnosed with COVID-19-induced immune thrombocytopenic purpura (ITP). Commonly seen in cases with COVID-19-vaccine-induced thrombocytopenia, there are very few published case reports of ITP as a result of the COVID-19 virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have found that the incidence of thrombotic complications is 16–69% in patients with COVID-19 admitted to intensive care. Also, mild thrombocytopenia was presented in 70%- 95% of COVID-19 patients 25 , 26 . Cases of TMA have been sporadically reported in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the incidence of thrombotic complications is 16–69% in patients with COVID-19 admitted to intensive care. Also, mild thrombocytopenia was presented in 70%- 95% of COVID-19 patients 25 , 26 . Cases of TMA have been sporadically reported in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we excluded patients with COVID-19 to match the inclusion criteria of a previous similar study by Han,et al [6]. This was also because COVID-19 has been linked to thrombocytopenia of varying degrees, as reported in previous studies, case reports, and case series [19,[31][32][33][34][35][36][37][38]. Thus, we wanted to exclude this condition as a potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia can also occur in the context of SARS-CoV-2 infection due to various mechanisms. Immune thrombocytopenia has been reported as a complication of COVID-19, potentially due to factors such as molecular mimicry, immune dysregulation, cryptic antigen expression on platelets, and epitope spreading [15][16][17]. No studies thus far have directly compared the incidence of ITP following SARS-CoV-2 infection and mRNA COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%